Small Molecule Follicle-Stimulating Hormone Receptor Agonists and Antagonists - Anderson, Ross C.; Newton, Claire L.; Millar, Robert P. (Frontiers in Endocrinology, 2019)
The follicle-stimulating hormone receptor (FSHR) has been targeted therapeutically for decades, due to its pivotal role in reproduction. To date, only purified and recombinant/biosimilar FSH have been used to target FSHR in assisted reproduction, with the exception of corifollitropin alfa; a modified gonadotropin in which the FSH beta subunit is joined to the C-terminal peptide of the human choriogonadotropin beta subunit, to extend serum half-life. Assisted reproduction protocols usually entail the trauma of multiple painful injections of FSH to initiate and promote folliculogenesis, which has prompted the development of a number of orally-available low molecular weight (LMW) chemical scaffolds targeting the FSHR. Furthermore, the recently documented roles of FSHR in diverse extragonadal tissues and conditions, such as cancer, fat metabolism and bone density regulation, has highlighted the potential utility of LMW modulators of FSHR activity. Despite these chemical scaffolds encompassing a spectrum of in vitro and in vivo activities and pharmacological profiles, none have yet reached the clinic. In this review we discuss the major chemical classes of LMW molecules targeting the FSHR, and document their activity profiles and current status of development, in addition to discussing potential clinical applications.